Superdisintegration: A Review Update and Application - Narke, Ramakant M.; Kaspate, D. S.; Kulkarni, G. S.; Chintamani, R. B. (Asian Journal of Pharmaceutical Research and Development, 2014)
The need of improved palatability in orally administered products has encouraged the development of numerous formulations with improved performance and acceptability. Orally disintegrating tablets are an emerging trend in novel drug delivery system and have received ever-increasing demand during the last few decades. The field has become a rapidly growing area in the pharmaceutical industry and gaining popularity due to ease of administration and better patient compliance especially for geriatric and pediatric patients. Disintegration plays a most important role in improving the drug activity and hence increases the patient compatibility. The therapeutic activity of the formulations is obtained by disintegration followed by dissolution. The inclusion of right disintegrant is a prerequisite to get optimal bioavailability in tablets and capsules. Disintegrants are the substances that cause the rapid disintegration of the capsules or tablets into smaller particles that dissolves more rapidly than in the absence of the disintegrants. On the other hand superdisintegrants, as it name suggests superior to disintegrants are the substances which facilitates or increases the disintegration time even at low level ,typically 1-10% by weight relative to the total weight of the dosage unit. This review is focused on a variety of natural and synthetic superdisintegrants and their modification to improve disintegration property and efficiency.